Genesis of a Poetics of Silence - Enora Lessinger (Sillages Critiques)
The concept of a poetics of silence has acquired a central place in literary theory in recent decades, with unreliable narration as defined by Booth (1961) playing an important part in the conceptualisation of an aesthetics of silence. Both silence and unreliable narration are key components of Kazuo Ishiguro’s writing strategy. I want to show that the poetics of silence that is so constitutive of his style was already at work at the very beginning of his writing. In order to achieve this goal, this paper studies one of Ishiguro’s first published short stories, “A Strange and Sometimes Sadness” (1981), in which a first-person narrator evokes memories of her time in Nagasaki during World War II. The narrator progressively turns out to be an unreliable one, due to the unspeakability of her traumatic experience. Her reluctance to report certain facts and to express some of her feelings is emphasised by the overabundance of details provided on safer subjects. The implied reader is compelled to try and fill the text’s blanks, which themselves shed light on the gap between narrator and implied author. This short story prefigures very clearly Ishiguro’s later novels, and deals with themes dear to him: memory, family, trauma and guilt, the atomic bomb as an absent centre. It also presents a very clear picture of the genesis of his writing style, centred around a poetics of silence, both at the diegetic and narratorial levels.